2005
DOI: 10.1097/01.brs.0000182275.31425.cd
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Pedicle Screws: Conventional Versus Computer-Assisted Placement of Cannulated Screws

Abstract: Transpedicular screws in the cervical spine and cervicothoracic junction can be applied safely and with high accuracy in a conventional technique. Cannulated screws and the use of separate stab incisions from C3-C6 with a trocar system allow for reduced screw misplacement rates. The CAS system leads to significantly reduced screw misplacement rates. Therefore, because of the potential risk of injury to the vertebral artery and neural elements, the use of a CAS system seems to be beneficial, especially for pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
165
0
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(175 citation statements)
references
References 35 publications
3
165
0
7
Order By: Relevance
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…At review, 48 papers were excluded as they did not meet the inclusion criteria (Table 1). Thus, 23 publications [5,6,8,9,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] were analysed in this paper (Table 2; 2 randomised controlled trials, 12 case-control studies and 9 case series). Three studies were in German language and remaining 20 studies were in English.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies [12,13,19,24,26,30] reported follow-up period ranging from 15 to 34 months, while one study followed the patients to clinical and radiological bony fusion [16], but none reported on rate of fusion achieved.…”
Section: Fusion Ratementioning
confidence: 99%
See 1 more Smart Citation
“…Although computer-assisted navigation has been used in craniofacial surgery, joint arthroplasty, trauma, and spine surgery [1,4,7,8] for some time, its application in orthopaedic bone tumor surgery is more recent [2,3,5,6,9]. To date, there is no software designed specifically for surgery on long bone and pelvic tumors.…”
Section: Introductionmentioning
confidence: 99%
“…However, this technique has a potential risk of nerve root, spinal cord and vertebral artery injury due to a small corridor of safe screw placement [31,39,41], recent clinical studies demonstrate that relevant complications do not occur frequently [2,9,11,15,18,24,26,29,47,48]. The axis of the cervical pedicles to the sagittal midline plane vary between 25 and 60°and makes a wide exposure of the spine necessary [14].…”
Section: Introductionmentioning
confidence: 99%